Indwelling Pleural Catheter Placement for Nonmalignant Pleural Effusions - Bramley, Kyle; DeBiasi, Erin; Puchalski, Jonathan (Seminars in Respiratory and Critical Care Medicine, 2018)
Pleural effusions account for significant symptoms and morbidity. Recent studies demonstrate a high mortality in patients with “benign” pleural effusions, now better characterized as nonmalignant pleural effusions (NMPEs) based on their prognosis. The most common nonmalignant clinical conditions with recurrent pleural effusions are congestive heart failure and hepatic hydrothorax, although many other diseases exist in isolation or as comorbid conditions. When conventional therapy fails, thoracentesis is often performed for relief of dyspnea. Many times, however, the effusions recur despite maximal medical therapy. Placement of tunneled or indwelling pleural catheters provides an effective therapeutic strategy for recurrent NMPEs when other medical therapy fails.
Keywords: benign pleural effusion; nonmalignant pleural effusion; tunneled pleural catheter; indwelling pleural catheter